Ultrasensitive pathogen detection with a rolling circle amplification-empowered multiplex electrochemical DNA sensor - Yeap, Cheryl S Y; Chaibun, Thanyarat; Lee, Su Yin; Zhao, Bin; Jan, Yuan; La-O-Vorakiat, Chan; Surareungchai, Werasak; Song, Shiping; Lertanantawong, Benchaporn (Chemical communications (Cambridge, England), 2021)
We report a highly sensitive and selective multiplex assay by empowering an electrochemical DNA sensor with isothermal rolling circle amplification. The assay could simultaneously detect and discriminate three common entero-pathogens in a single reaction, with femtomolar sensitivity. It is useful for field- or resource-limited settings.
Keywords: elektrochemické techniky; Electrochemical Techniques; biosenzitivní techniky; Shigella flexneri; Vibrio cholerae; DNA; Salmonella typhi; techniky amplifikace nukleových kyselin; Nucleic Acid Amplification Techniques; Biosensing Techniques